2019
DOI: 10.1029/2019gl085498
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic Control Over Wintertime Oxidation of Atmospheric Pollutants

Abstract: During winter in the midlatitudes, photochemical oxidation is significantly slower than in summer and the main radical oxidants driving formation of secondary pollutants, such as fine particulate matter and ozone, remain uncertain, owing to a lack of observations in this season. Using airborne observations, we quantify the contribution of various oxidants on a regional basis during winter, enabling improved chemical descriptions of wintertime air pollution transformations. We show that 25-60% of NO x is conver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 66 publications
3
32
1
Order By: Relevance
“…The Wintertime INvestigation of Transport, Emissions, and Reactivity (WINTER) mission was designed to understand the processes controlling atmospheric composition in the wintertime boundary layer of the Eastern U.S. A recent analysis of these observations has revealed that HCHO can be as much as 50% of the daily integrated radical source (Haskins et al, 2019). Furthermore, Jaeglé et al (2018) found a bias of −46% in GEOS-Chem simulated HCHO concentrations relative to WINTER observations at altitudes < 1 km.…”
mentioning
confidence: 99%
“…The Wintertime INvestigation of Transport, Emissions, and Reactivity (WINTER) mission was designed to understand the processes controlling atmospheric composition in the wintertime boundary layer of the Eastern U.S. A recent analysis of these observations has revealed that HCHO can be as much as 50% of the daily integrated radical source (Haskins et al, 2019). Furthermore, Jaeglé et al (2018) found a bias of −46% in GEOS-Chem simulated HCHO concentrations relative to WINTER observations at altitudes < 1 km.…”
mentioning
confidence: 99%
“…The highest winter concentrations of ClNO2 to date were observed in southern China, with a maximum level of 4.7 ppbv at a mountain top in Hong Kong in aged urban/industrial plumes from the Pearl River Delta (PRD) (Wang et al, 2016) and 8.3 ppbv during a severe pollution episode within the PRD (Yun et al, 2018 and ppbv found by Yun et al, 2018), which contrasts the high concentrations of PM2.5 and low concentrations of O3 over northern China during the cold winter. The winter mixing ratios of ClNO2 in the US and Europe range from approximately 0.3 ppbv in urban California (Mielke et al, 2016) and urban Manchester (Priestley et al, 2018), respectively, to 1.3 ppbv in the outflow of coastal urban areas (Riedel et al, 2013;Haskins et al, 2019). In general, the winter concentrations of ClNO2 over northern China were comparable to or slightly higher than those observed in the US and Europe.…”
Section: Overall Measurements Diurnal Patterns and Comparison With Omentioning
confidence: 78%
“…Subsequent studies demonstrated the worldwide ubiquity of ClNO2 and confirmed its significant role in photochemistry (Thornton et al, 2010;Mielke et al, 2011;Phillips et al, 2012;Edwards et al, 2013;Bannan et al, 2015;Wild et al, 2016;Wang et al, 2016;Bannan et al, 2019;Eger et al, 2019). The role of ClNO2 in the radical budget could be more important than that of OH in winter, because OH production is reduced in winter owing to lower concentrations of O3 and H2O vapor in this season (Haskins et al, 2019). A limited number of winter observations of ClNO2 have been conducted on various platforms, including on aircrafts over northern Europe (Priestley et al, 2018) and the eastern US (Haskins et al, 2019), on a tall tower in Boulder, USA (Riedel et al, 2013), on a mountain top in Hong Kong (Wang et al, 2016), and at ground sites in Alberta, Canada (Mielke et al, 2016) and Heshan, China (Yun et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The broad influence of chlorine chemistry stems from the high reactivity of Cl atoms with many gas phase species, including methane (Atkinson, 1997), many volatile organic compounds (VOCs) (Simpson et al, 2015), dimethyl sulfide (Chen et al, 2017; Hoffmann et al, 2016), and mercury (Horowitz et al, 2017). Cl atoms can even be the dominant early‐morning oxidative agent in the winter, serving to increase OH production by enhancing formaldehyde through Cl atom‐initiated VOC oxidation and enhancing O 3 production from NO x recycling (Haskins et al, 2019).…”
Section: Introductionmentioning
confidence: 99%